A Morphometric Analysis to Investigate the Variations in the Number, Position, and Direction of Nutrient Foramina in the Clavicle - Md. Hassan Ali (Asian Journal of Medical Research, 2017)
Background: The clavicle is a horizontally positioned, bent, and modified long bone located at the base of the neck. It transfers the force exerted by the upper limb to the axial skeleton. A morphometric analysis to investigate the variations in the number, position, and direction of nutrient foramina in the clavicle. Methodology: It was at the department of Anatomy that this research was carried out. In this investigation, we included a total of fifty dried clavicle bones from human subjects. Studying lasted for a total of one year during the course of its existence. Those bones that were injured, misshapen, or had a significant pathological anomaly were not included in the research under consideration. All of the clavicles were examined to determine the number of nutritional foramina, as well as their position, location, and orientation within. In order to analyze the data, Microsoft Excel was used. Results: For this work, we examined 50 desiccated human clavicle bones and made macroscopic observations. We discovered that a single foramen was present in 66% of the bone samples. Among the clavicle bones, 26% had two nutrient foramen, whereas 8% had three nutrient foramen. The research found that 62% of nutritional foramen were located on the inferior surface, 36% were located on the posterior surface, and 2% were located on the superior surface. There were nutritional foramen present at a rate of 10% in the medial 1/3rd, 68% in the middle 1/3rd, and 22% in the lateral 1/3rd. Conclusion: It may be inferred that the clavicle has a single nutrient foramen that is mostly located on the lower surface. The nutritional foramen was most often found in the center one-third of the bone length, followed by the lateral one-third and finally the medial one-third. The nutritional foramen was oriented towards the acromial end. The results of this research may be used to protect the blood flow in surgical procedures such as internal fixation and vascularized bone graft.